Model-independent measurement of charm mixing parameters in B[bar]→D0(→K0Sπ+π−)μ− ν[bar]μX decays - Aaij, Roel; Archilli, Flavio; Bachmann, Sebastian; Berninghoff, Daniel; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Gerick, David; Grabowski, Jascha; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review, 2023)
A measurement of charm mixing and CP-violating parameters is reported, using ¯B→D0(→K0Sπ+π−) μ−¯νμX decays reconstructed in proton-proton collisions collected by the LHCb experiment during the years 2016 to 2018, corresponding to an integrated luminosity of 5.4 fb−1. The measured mixing and CP-violating parameters are xCP=[4.29±1.48(stat)±0.26(syst)]×10−3, yCP=[12.61±3.12(stat)±0.83(syst)]×10−3, Δx=[−0.77±0.93(stat)±0.28(syst)]×10−3, Δy=[3.01±1.92(stat)±0.26(syst)]×10−3. The results are complementary to and consistent with previous measurements. A combination with the recent LHCb analysis of D*+→D0(→K0Sπ+π−)π+ decays is reported.
*LHCb Collaboration: R. Aaij, F. Archilli, S. Bachmann, D. Berninghoff, M. Borsato, R. Caspary, G. Frau, D. Gerick, J.P. Grabowski, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, R. Kopecna, B. Leverington, P. Li, J. Marks, D.J. Unverzagt, U. Uwer, C. Witola, A. Zhelezov (und 1044 weitere Personen)
Im Titel sind die Zahl 0 sowie die Plus- und Minuszeichen hochgestellt, der Buchstabe S und das 2. Zeichen mu sind tiefgestellt
Im Titel steht der Buchstabe B sowie das Zeichen nu mit einem Oberstrich
Gesehen am 21.05.2024